Pengelolaan Wilayah Pesisir Terpadu sebagai Upaya Pemberdayaan Ekonomi di Banyuwangi - Ahmad Najib Rabbani (Jurnal Inovasi dan Pengabdian, 2025)
This article discusses strategies to improve the economic empowerment of coastal communities through the ICZM (Integrated Coastal Zone Management) approach. As an archipelagic country, Indonesia has great natural resource potential in coastal areas. However, coastal communities often face complex socio-economic challenges. Through the ICZM approach, concrete steps such as creating alternative jobs, bringing communities closer to new sources of capital and technology, and building solidarity and collective action in the community can be taken to improve their economic empowerment. By involving various parties such as the Ministry of Marine Affairs and Fisheries, local governments, and non-governmental organizations, it is hoped that these efforts can have a positive impact on coastal communities in managing their economic efforts effectively. This approach is carried out using a qualitative descriptive approach based on a literature review.